Diagnostic Accuracy of EndoFaster® and Narrow-Band Imaging Endoscopy in Patients with Impaired Gastric Acid Secretion: A Real-Time Prospective Study - M. Cazzato; G. Esposito; G. Galli; E. Pilozzi; E. Lahner; V. D. Corleto; A. Zullo; E. Di Giulio; B. Annibale (Gastroenterology Research and Practice)
Background. EndoFaster® analyzes gastric juice in real time during gastroscopy allowing the detection of hypo-achlorhydric conditions, like corpus atrophic gastritis. Narrow-band imaging (NBI) endoscopy allows to accurately detect and perform target biopsies in areas of intestinal metaplasia, a histological change often associated to corpus atrophic gastritis. Aims. To compare the diagnostic accuracy of EndoFaster® with histological evaluation for corpus atrophic gastritis through high-resolution (HR) NBI targeted biopsies. Methods. Prospective study on consecutive adult patients undergoing gastroscopy between April and November 2018. Patients in therapy with proton pump inhibitors, previous gastric surgery, and/or known gastric neoplasia were excluded. At the beginning of gastroscopy, gastric juice was aspirated and analyzed by EndoFaster® in 15 seconds. Endoscopists were blinded to the report of EndoFaster®. Evaluation of gastric mucosa in HR-white light was firstly performed, then with HR-NBI allowing to perform targeted biopsies on areas suspected for intestinal metaplasia; otherwise, biopsies were performed according to the updated Sydney System protocol and sent for histopathological evaluation. Results. Overall, 124 patients were included [64% F; 56 (18-85) years]. Corpus atrophic gastritis was present in 41.9% of patients. EndoFaster® showed an accuracy for corpus atrophic gastritis diagnosis, compared to histopathological evaluation as gold standard, of 87.1% and a sensitivity, specificity, PPV, and NPV of 78.8%, 93.1%, 89.1%, and 85.9%, respectively. pH showed a positive correlation with the severity score of atrophy (r=0.67, 95% CI: 0.73-0.81, and p<0.0001). EndoFaster® allowed to diagnose corpus atrophic gastritis in 3.7% of patients negative to NBI (corpus atrophic gastritis without intestinal metaplasia). Conclusion. EndoFaster® seems a promising tool to diagnose corpus atrophic gastritis. The evaluation of hypo-achlorhydria during gastroscopy can address bioptic sampling in corpus atrophic gastritis patients without intestinal metaplasia.